The RANKL inhibitor denosumab in combination with dual checkpoint inhibition is associated with increased CXCL-13 serum concentrations - Schaper-Gerhardt, Katrin; Gutzmer, Ralf; Angela, Yenny; Zimmer, Lisa; Livingstone, Elisabeth; Schadendorf, Dirk; Hassel, Jessica C.; Weishaupt, Carsten; Remes, Bernhard; Kubat, Linda; Spassova, Ivelina; Becker, Jürgen C. (European journal of cancer, 2024)
BACKGROUND: Recent evidence suggests additional immunomodulatory properties of RANKL inhibition possibly boosting the clinical efficacy of immune checkpoint inhibitors (ICI). - METHODS: We conducted a prospective, multicentre clinical trial in unresectable stage IV melanoma patients with bone metastases who received denosumab in parallel with dual ICI (BONEMET) and performed comprehensive immune monitoring at baseline and 4, 12, and 24 weeks after initiation of therapy. Secondary endpoints included tolerability and efficacy. For comparison, biospecimens from melanoma patients treated with dual ICI without denosumab were analyzed accordingly and served as retrospective reference cohort. - RESULTS: In both the BONEMET (n = 16) and the reference cohort (n = 18) serum levels of 17 cytokines, including IFNγ were significantly increased after 4 weeks of treatment. Patients who received ICI and denosumab showed a significantly higher increase in serum CXCL-13 and a significant decrease in VEGFc compared with the reference cohort. While no changes in T cell composition were observed at 4 weeks, patients in the BONEMET cohort showed a significant decrease in the peripheral naïve T-cell population and an increase in CD8+ effector cells after 12 weeks. Treatment-related adverse events occurred with comparable frequency (93.8% in the BONEMET cohort versus 83.3% in the reference cohort). 7/16 patients in the BONEMET cohort and 8/18 patients in the reference cohort achieved disease control. - CONCLUSION: Denosumab in combination with dual ICI modulates cytokine expression and T-cell composition in peripheral blood. The upregulation of CXCL-13, a key factor for initiating tertiary lymphoid structures, strengthens the hypothesis that denosumab indeed boost immunological effects.
Online veröffentlicht: 2. März 2024
Gesehen am 25.03.2025